Synthesis of Axially Chiral N‐Arylindoles via Atroposelective Cyclization of Ynamides Catalyzed by Chiral Brønsted Acids - Wang, Ze‐Shu; Zhu, Lu‐Jing; Li, Cui‐Ting; Liu, Bin‐Yang; Hong, Xin; Ye, Long‐Wu (Angewandte Chemie International Edition, 2022)
In recent years, asymmetric catalysis of ynamides has attracted much attention, but these reactions mostly constructed central chirality, except for a few examples on the synthesis of axially chiral compounds which exclusively relied on noble‐metal catalysis. Herein, a facile access to axially chiral N‐heterocycles enabled by chiral Brønsted acid‐catalyzed 5‐endo‐dig cyclization of ynamides is disclosed, which represents the first metal‐free protocol for the construction of axially chiral compounds from ynamides. This method allows the practical and atom‐economical synthesis of valuable N‐arylindoles in excellent yields with generally excellent enantioselectivities. Moreover, organocatalysts and ligands based on such axially chiral N‐arylindole skeletons are demonstrated to be applicable to asymmetric catalysis. A chiral Brønsted acid‐catalyzed atroposelective cyclization of ynamides is disclosed, which represents the first metal‐free protocol for the construction of axially chiral compounds from ynamides. This method enables the practical and atom‐economical synthesis of valuable N‐arylindoles in excellent yields with generally excellent enantioselectivities.